KARAKTERISTIK DAN PARAMETER SUBDUKSI SUMBER GEMPA PULAU JAWA - Wisnu Erlangga (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2020)
The movement of three large plates makes earthquakes frequent in Indonesia. The earthquake caused a lot of damage and casualties. One of the causes of the high risk of earthquake disasters is the large population. Java Island is the island that has the largest population in Indonesia. In addition, earthquakes often occur in Java and its surroundings, which cause a very high risk of earthquake. A further disaster that occurs after an earthquake is a tsunami if the earthquake originates from the ocean (earthquake originates from subduction). Therefore, this study examines the characteristics and parameters of earthquakes originating from subduction around Java Island which consists of 10 zones (5 of megathrust zone and 5 of benioff zone). The method used to determine these parameters is the Guternberg-Richter's law method and the maximum likely hood / characteristic method. The results of these two methods have differences due to earthquake uncertainty factors. In the application of earthquake hazard analysis, these two methods are used for calculations by increasing the percentage of use in the characteristic method. This is because geological evidence shows that characteristic earthquakes occur more frequently than earthquakes predicted from the gutenberg-richter model. In addition, it is also necessary to know the subduction zone dip angle for modeling 3D earthquake sources. Each subduction zone around the Java Island is divided into 5 areas. The megathrust zone is at a depth of up to 50 km and the benioff zone at a depth of more than 50 km. The result shows that the largest dip value is in the Java 3 megatrust zone with 14.667 and the Java 2 benioff zone with 53.667.